Kurangnya Komunikasi dalam Keluarga sebagai Problematika Sosial Modern - Suci Setiawati; Achmad Hufad; Yani Achdiani (Journal of Government and Social Issues (JGSI), 2026)
Lack of communication within the family is a modern social problem increasingly encountered in everyday life. Changes in societal lifestyles, work demands, and rapid technological developments mean that interactions between family members are no longer as intense as they once were. Many parents are preoccupied with work, while children spend more time on their devices or doing activities outside the home. As a result, opportunities to talk, share stories, or simply listen to one another are diminishing. This situation gradually impacts the quality of family relationships. When communication is poor, misunderstandings become more likely. Small issues that should be resolved with simple conversations can escalate into larger conflicts. Furthermore, a lack of communication also strains emotional bonds between family members. The mutual trust, openness, and warmth that should exist within a family can fade over time